UNMANNED NUCLEAR POWER PLANT AREA FOR SAFETY AND REMOTE ACCESS USING WIFI AND INTERNET OF THINGS - Bhargav, B.; subitha, D. (International Journal of Psychosocial Rehabilitation, 2020)
The safety in the nuclear power station process is needed to save the number of human’s life. The nuclear stations are deployed in the areas where the large amount of uranium and thorium is used. So at the period the monitoring of the various parameters of nuclear stations we use corresponding sensors. In this paper wepropose the monitoring of the light detection, leakage of the gas, temperature, humidity. The sensors are connected to the controller. When the sensor range is exceeded above the threshold value the buzzer will be ON to give the alert message is given. LDR sensor is used which can sense the presence of light. All the sensor data are updated in the IOT. The WIFI module is used in transmitting and receiving the data in the clouds. The data are plotted in the form of graph at each interval of time the cloud data is get updated. The data communication to the cloud occurs at the baud rate of 115200. This method can helpful in saving the employees in the danger situation.